Characterization of Stretchable Interconnects Fabricated Using a Low Cost Metallization Transfer Process onto PDMS. (12th August 2015) - Hilbich, D.; Yu, G.; Gray, B. L.; Shannon, L.
Abstract : The growing number of applications requiring conformal electronic devices incorporated into unconventional and dynamic surfaces has led to an increase in the development of stretchable electronics. Together with novel materials and fabrication processes, innovative conductive patterns are being developed in order to meet the needs of modern applications. Here, we present the design, fabrication, and characterization of first-order curved Peano structures fabricated using a newly developed thick film copper metallization transfer process onto PDMS. In order to maximize the stretchability of these structures, we present a characterization and analysis of the relationship between relative resistance and tensile strain in fabricated devices while systematically varying the geometric parameters of various curve designs. The response of the structures to cyclic failure and recovery is also characterized. These results demonstrate that the newly developed transfer process can be used to fabricate stretchable Peano curves and provide insight into the geometric optimization of these curves in stretchable electronics applications.